Characterization and processing parameters of poly(vinyl alcohol)-tapioca starch for injection moulding [electronic resource] - Mohd. Shahrul Nizam Salleh, 1985-; Fakulti Kejuruteraan Kimia (2010)
Thesis (Sarjana Kejuruteraan (Polimer)) - Universiti Teknologi Malaysia, 2010